องค์ประกอบทางเคมีและฤทธิ์ยับยั้งแซนทีนออกซิเดสจากเปลือกต้นเปล้าใหญ่ Croton oblongifolius Roxb.จากอำเภอภูเรือ จังหวัดเลย - สุธินี แสงอรุณ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The stem barks of Croton oblongifolius Roxb. were extracted with hexane, ethyl acetate and methanol, respectively. The extracts were separated by column chromatography on silica gel. Four compounds were isolated and identified, namely, a mixed steroid of stigmasterol, β-sitosterol และ campesterol (1), two clerodane diterpenoids rhich were (-)-hardwickiic acid (2), (-)-20-benzyloxyhardwickic acid (3) and a labdane diterpenoid which was (-)-Nidorellol (4). The structures of the isolate compounds were identified using their physical properties and spectroscopic data. They were tested for xanthine oxidase inhibition and it was found that Compound 1 showed strong inhibitory activity on xanthine oxidase with IC50 90 µg/ml while Compound 3, Compound 4 and Compound 2 showed only weak activity with IC50140, 155 และ 190 µg/ml, respectively.